Quality of glycemic control in type 2 diabetes mellitus (T2DM) and its association with markers of coagulation and inhibitors of fibrinolysis: A case–control study in the Upper West Region, Ghana - Peter K. Selleh; Enoch O. Anto; Wina I. O. Boadu; Benedict Sackey; Lilian A. Boateng; Charles Nkansah; Frederick Nsafoah; Abdul R. Saasi; Selina Mintaah; Yaw A. Wiafe; Charles Derigubah; Emmanuel E. Korsah; et al. (Health Science Reports, 2023)
Abstract Background and Aims Type 2 diabetes mellitus (T2DM) individuals are at a higher risk of developing diabetes complications, with approximately 80% complication‐related mortality. The increased morbidity and mortality among T2DM patients are partly due to dysregulated hemostasis. This study determined the quality of glycemic control in T2DM and its association with markers of coagulation and inhibitors of fibrinolysis. Methods This case–control study recruited 90 participants involving: 30 T2DM patients with good glycemic control, 30 with poor glycemic control, and 30 nondiabetic subjects as controls at a Municipal Hospital in Ghana. Fasting blood glucose, glycated hemoglobin, activated partial thromboplastin time (APTT), prothrombin time (PT), calculated international normalized ratio (INR), and full blood count (FBC) were determined for each respondent. Plasma levels of plasminogen activator inhibitor‐1 (PAI‐1) and thrombin activatable fibrinolysis inhibitor (TAFI) were determined using the solid‐phase sandwich enzyme‐linked immunosorbent assay method. Data were analyzed using R language software. Results Plasma PAI‐1 antigen levels were significantly higher in the participants with poor glycemic control as compared to participants with good glycemic control (p < 0.0001). There was no significant difference in plasma TAFI levels between the participants with poor glycemic control as compared to participants with good glycemic control (p = 0.900). T2DM patients had significantly shorter APTT, PT, and INR than controls (p < 0.05). At a cut‐off of ≥161.70 pg/μL, PAI was independently associated with increasing odds (adjusted odds ratio = 13.71, 95% confidence interval: 3.67–51.26, p < 0.0001) of poor glycemic control and showed the best diagnostic accuracy for poor glycemic control (area under the curve = 0.85, p < 0.0001). Conclusion PAI‐1 levels were significantly increased in T2DM with poor glycemic control and emerged as the best predictor for poor glycemic control. Good glycemic management to control the plasma levels of PAI‐1 is required to prevent hypercoagulability and thrombotic disorders.